1999
DOI: 10.1136/jcp.52.5.350
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical expression of pi class glutathione S-transferase in the basal cell layer of benign prostate tissue following chronic treatment with finasteride.

Abstract: Background-Glutathione S-transferases (GST) may prevent carcinogenesis through inactivation of reactive electrophiles by conjugation to reduced glutathione. Treatment directed at the induction or preservation of GST-expression in normal epithelium could have a profound impact on the prevention of prostate neoplasia. Finasteride, a 5--reductase inhibitor, is used as a chemopreventive agent because it blocks the conversion of testosterone to its byproduct which promotes prostate tumour growth. Objective-To inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 23 publications
2
13
0
Order By: Relevance
“…In agreement with other reports [37][38][39][40][41][42][43], we found that GSTp was a reliable marker of basal cells in benign acini. This is similar to the distribution of CuZn-superoxide dismutase, another free radical scavenger [44,45].…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with other reports [37][38][39][40][41][42][43], we found that GSTp was a reliable marker of basal cells in benign acini. This is similar to the distribution of CuZn-superoxide dismutase, another free radical scavenger [44,45].…”
Section: Discussionsupporting
confidence: 93%
“…This is in agreement with a previous study by our group. 36 No substantial diVerences were seen between the samples from patients with benign prostatic hyperplasia and those derived from patients unaVected by this disease. Our findings are in agreement with the data derived from a biochemical study performed by Tew et al 35 De Marzo and colleagues 37 proposed that most proliferating cells in normal prostate and benign prostatic hyperplasia tissue reside in the basal cell compartment.…”
Section: Discussionmentioning
confidence: 91%
“…When basal cells are not present, such as in the gaps present in the basal cell layer, the luminal cells might take up this protective role. 36 It is possible that the early loss of GST-expression in human prostate cells might compromise their electrophilic defences, making them vulnerable to the accumulation of the genetic damage necessary to foster the neoplastic transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Many genes and proteins have been reported that show increased levels of expression as a result of neoplastic transformation of prostate cells. Most of these molecules are expressed also in basal epithelial cells in normal prostate (Blok et al, 1995;Reiter et al, 1998;He et al, 1997;Troyer et al, 1995;Montironi et al, 1999;Guate et al, 1997), and thus their expression in tumor cells can be considered a re¯ection either of the expansion of a population of proliferating cells, or the activation in tumor cells of pathways that are operative in normal proliferation. On the other hand, some genes and proteins overexpressed in prostate cancer cells are not expressed, or are not detectable, in normal prostate (Magi Galluzzi et al, 1997;Zhau et al, 1992).…”
Section: Discussionmentioning
confidence: 99%